A study of association of smoking with salivary parameters and common oral diseases among adults attending government dental clinics in Kota Bharu, Kelantan - Mohd Zulkarnain, Sinor (2008)
The etiology and pathogenesis of dental caries and periodontal disease are multifactorial. Reduction in quality of saliva parameters and smoking can play a role in triggering the initiation and progression of dental disease To determine the effect of smoking with salivary parameters and common oral diseases among adults attending the government dental clinics in Kota Bharu, Kelantan This is a cross sectional study of patients aged 20 years and above attending government dental clinics in Kota Bharu. 220 patients who fulfilled inclusion and exclusion criteria were selected at every 1Oth interval of which 73 were smokers and 147 non smokers. Caries experiences were calculated using DMFT index while periodontal disease was measured using CPI index score. Saliva properties were assessed using BUFFER@ TEST KIT- by G/C Co. Data were analyzed using SPSS version 12.0 SPSS inc. USA No association between smoking and resting pH. Number of cigarette consumed have positive association on resting salivary flow rate with R2=0.082. Smoking shows positive association with stimulated salivary flow rate with R2=0.088; smoking and sex showed negative association with buffering capacity of saliva but the association was weak with R2=0.043 Regarding smoking influence on DMFT; duration of smoking showed positive association with R2=0.368. For number of filled tooth, smoking has negative association. Smoking showed positive association with increase risk of developing periodontal disease. Resting pH and stimulated flow rate have association with DMFT score. However, only resting saliva flow rate have significant association with periodontal disease, i.e. increase saliva flow was observed in periodontal disease patientsIt was concluded that increasing number of cigarettes consumed per day will increase resting saliva flow, and, smokers have low saliva buffering capacity. Smoking duration has positive association with DMFT score, i.e. number of filled tooth was less in smoking group. There is increase risk of having periodontal disease among smokers. Reducing saliva pH and stimulated flow rate will increase the risk for caries formation. Positive association was observed between resting saliva and periodontal disease.